Overview of Teaching Strategies: Examining the Influence of Effective Teaching Strategies on Learning Outcomes (Journal of Advances and Scholarly Researches in Allied Education, 2019)
This study aimed to find out the impact of effective teaching strategies on producing fast and good learning outcomes. This paper focuses on teaching strategy as a generalized plan for a lesson which includes structure, instructional objectives and an outline of planned tactics, necessary to implement the strategies